Flow and volume response to bronchodilator in patients with COPD - Vigna, Matteo; Aiello, Marina; Bertorelli, Giuseppina; Crisafulli, Ernesto; Chetta, Alfredo (Acta Biomedica Atenei Parmensis, 2018)
The response to a bronchodilator is considered as crucial to diagnose COPD and to distinguish COPD from asthma. COPD is characterized by progressive airflow obstruction that is only partly reversible, whereas asthma is associated with airflow obstruction that is often reversible either spontaneously or with treatment. In spite of the partly reversible airflow obstruction, patients with COPD may show a significant bronchodilator response both in terms of an increase in forced expiratory volume in 1 second (FEV1) or in forced vital capacity (FVC) after an adequate dose of an inhaled bronchodilator. Changes in FEV1 or FVC characterize, respectively, flow or volume response after bronchodilator administration. This overview will deal with the reversibility testing characteristics and its clinical significance in COPD patients.